2017
DOI: 10.4314/ijbcs.v10i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Étude comparative du développement de <i>Bactrocera dorsalis</i> (Hendel) (Diptera : Tephritidae) sur <i>Irvingia gabonensis</i> et <i>Musa</i> sp.

Abstract: RESUMEBactrocera dorsalis est la Tephritidae la plus nuisible à la production fruitière au Bénin. Son introduction en 2004 a été à l'origine de l'accroissement des dégâts et des pertes économiques. Des travaux de recherche se sont orientés vers l'étude de sa biologie par la mise au point d'une colonie de laboratoire par des méthodes simples et peu coûteuses. L'objectif de cette étude était d'identifier parmi les fruits usuels disponibles sur le marché tout au long de l'année, le meilleur substrat pour la ponte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
0
0
3
Order By: Relevance
“…Among the 7 host plants associated with B. dorsalis, the mango (M. indica) was the most infested cultivated fruit and the African apple (I. gabonensis) the most infested wild fruit. This result was consistent with those of Mwatawala et al (2006), Vayssières et al (2014), Hintenou et al (2016, Zida et al (2020) who showed that B. dorsalis preferentially infested cultivated fruits such as mango, guava, shea and wild fruits like I. gabonensis. Furthermore, B. dorsalis is a species of great economic importance in West Africa with a proliferation period that coincides with the ripening of mangoes and the rainy season (Mwatawala et al, 2006;Vayssières et al, 2014;Mutamiswa et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Among the 7 host plants associated with B. dorsalis, the mango (M. indica) was the most infested cultivated fruit and the African apple (I. gabonensis) the most infested wild fruit. This result was consistent with those of Mwatawala et al (2006), Vayssières et al (2014), Hintenou et al (2016, Zida et al (2020) who showed that B. dorsalis preferentially infested cultivated fruits such as mango, guava, shea and wild fruits like I. gabonensis. Furthermore, B. dorsalis is a species of great economic importance in West Africa with a proliferation period that coincides with the ripening of mangoes and the rainy season (Mwatawala et al, 2006;Vayssières et al, 2014;Mutamiswa et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…À cet effet, la masse optimale économique nécessaire qui pourrait être recommandée pour 100 larves est 90 g. L'intérêt de cette étude réside dans le fait que les produits importés coûtent très chers. La possibilité de trouver des produits locaux pour l'élevage de masse des parasitoïdes et des mouches des fruits pourrait aider à contrôler naturellement ces derniers (Hintenou et al, 2016). Alors, pour rentabiliser davantage l'élevage de B. dorsalis et F. arisanus en conditions de laboratoire, il serait nécessaire d'améliorer les conditions de laboratoire ou de travailler en milieu semi-naturel ; d'élargir la liste des supports alimentaires locaux et de procéder à des mélanges de substrats pour enrichir les milieux de production.…”
Section: Resultsunclassified
“…Pour réduire les dégâts de ces mouches, des méthodes de lutte variées ont été envisagées en intégrant la lutte biologique (Ouédraogo, 2011 ;N'depo et al, 2015). La lutte biologique fait l'objet d'un grand intérêt dans de nombreuses études car elle est l'une des composantes essentielles de la lutte intégrée et elle représente une approche agro-écologique (Gomina, 2015 ;Konta et al, 2015 ;Hintenou et al, 2016), c'est-à-dire respectueuse de l'environnement et viable sur le long terme.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It increased from 90,000 tonnes in 2017 to 200,000 tonnes in 2018, and in 2019, the production of 243,000 tonnes of mango was recorded according to the Association of Producers of Mango of Burkina Faso [3]. Unfortunately, the expansion of this sector is hampered by pests, including fruit and vegetable flies of the family Tephritidae [4]. Approximately 30 species of fruit flies have been inventoried in mango and citrus orchards, agroforestry parks and natural formations in the country [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%